The Bedford guide for college writers - Kennedy, X.J (Bedford/St. Martin's, 2008)
Rev. ed. of: The Bedford guide for college writers / X.J. Kennedy, Dorothy M. Kennedy, and Sylvia A. Holladay. 2002; Includes bibliographical references and indexes